Political Motives Behind a Single Candidate in Batanghari’s 2024 Local Election - Fajri, Syabina Laura; Subekti, Dimas; Pratiwi, Cholilla Suci; Muhammad, Hatta Abdi (Jurnal Transformative, 2025)
This research examines the political motive behind the formation of a grand coalition of political parties in the 2024 Batang Hari Regency Regional Head Election (Pilkada), which ultimately resulted in a single candidate. The research uses a qualitative approach with a case study design. Data was collected through in-depth interviews with political party elites, campaign teams, and local political observers, and was supported by documentation in the form of internal party regulations and media reports. The research results show variations in motives between parties. PPP and NasDem are driven by their structural proximity to the candidate pair. PAN, PKB, Demokrat, and Gerindra emphasize political efficiency. PKS demonstrates a control motive, while PKB, Golkar, and PDIP reflect a political security motive. these findings contribute to broader debates on local democracy by showing that the dominance of pragmatic coalition motives has significant implications for democratic quality. This research argues that the cross-ideological pragmatic coalitions that produce single candidates in local elections are not merely an electoral strategy, but a mechanism for consolidating elite power that directly reduces competition, voter choice, and local democratic accountability.